Biological delignification of rice straw using laccase from Bacillus ligniniphilus L1 for bioethanol production: A clean approach for agro-biomass utilization. (1st August 2022) - Nazar, Mudasir; Xu, Lingxia; Ullah, Muhammad Wajid; Moradian, Jamile Mohammadi; Wang, Yongli; Sethupathy, Sivasamy; Iqbal, Babar; Nawaz, Muhammad Zohaib; Zhu, Daochen
Abstract: The recalcitrance of lignocellulosic biomass due to severe lignification and complex cross-linking between lignin and cellulose fibers is a major hindrance in its clean and economical conversion to bioethanol. In the present study, the ligninolytic activity of purified bacterial laccase (BLac) from Bacillus ligniniphilus L1 was evaluated for delignification of rice straw for environment-friendly bioethanol production. BLac showed significant delignification activity at varying pH (3, 4, 7, and 9), and decreased the lignin (8.93%) and phenolic (44.8%) contents of rice straw. The chemical and structural changes in rice straw caused by BLac pretreatment determined via scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), and Fourier transform infrared (FTIR) spectroscopy confirmed the successful delignification of rice straw. BLac improved the cellulase (CL) hydrolysis of rice straw by releasing 15.8 mg/mL glucose and 21.8 mg/mL reducing sugar, and produced 22.3 mg/mL bioethanol. These findings indicate that BLac has the potential to efficiently utilize the rice straw resources for economical and environmentally feasible bioethanol production. Graphical abstract: Image 1 Highlights: BLac reduced lignin (8.93%) and phenolic contents (44.8%) of rice straw. BLac enhanced the release of glucose (15.8 mg/mL) and reducing sugar (21.8 mg/mL). BLac caused significant physicochemical changes in rice straw biomass. High ethanol production (22.3 mg/mL) from rice straw via BLac pretreatment.